Screening of antagonistic bacteria against fungal phytopathogens - Nina BOGDAN; Valerina SLANINA; Tamara SÎRBU; Ludmila BALAN; Robert Marian RUGINESCU (ACROSS)
Water samples, bottom sediments and biofilms of lake were investigated to the microbial diversity. One hundred twenty-two isolated microorganisms were identified by cultural, morphological and biochemical characteristics. Bacterial strains were screened to evaluate their ability to produce amylase, catalase, lipase and cellulase enzymes. Aquatic bacterial strains are active producers of valuable exoenzymes with antimicrobial properties. Isolates demonstrated developed enzymatic complex and antifungal activity against phytopathogens - Alternaria alternata, Botrytis cinerea, Fusarium solani, Fusarium oxysporum. Most active and stable to enzymatic and antifungal activities strains were identified as: Bacillus velezensis (Bacillus amyloliquefaciens) and Micrococcus yunnanensis (Micrococcus luteus) by PCR-based molecular analysis. Due to results of antagonistic activity in this study aquatic bacteria are promising for application in agriculture sector.